Composicion polifenolica de madera, corteza y hojas de Eucaliptus Camaldulensis. E. Globulus y E. Rudis - Conde, E.=700 1 Cadahia, E.; Garcia Vallejo, M.C.; Diez, R.
(En, Es)
ilus., 26 ref.
Keywords: EUCALIPTUS CAMALDULENSIS; EUCALIPTUS GLOBULUS; MYRTACEAE; COMPOSICION QUIMICA; MADERA; POLIFENOLES; FLAVONOIDES; ACIDOS FENOLICOS; ALDEHIDOS; QUIMIOTAXONOMIA; ESPAÑA